"Control interno en el manejo de inventarios y su relación con la rentabilidad de la empresa promoacabados, cantón Quevedo, año 2013" - Plaza Letourne, Olga Maribel (2016)
This research was conducted in the Republic of Ecuador, Provincia de los Rios, Quevedo Canton, which has the same small and medium enterprises engaged in the provision of services, trade, industry and agricultural and livestock production. The research was conducted in PROMOACABADOS, located in San Camilo, Manabi Street and Avenue # 347 Guayaquil, lasted six months, the overall objective was to evaluate the internal control system in the management of inventory and its relationship to the profitability of the Company "Promoacabados"; during which the following methods were applied: inductive, analytic and synthetic; also the types of research that are qualitative and quantitative, field and documentary are necessary for the collection of information, also the research design could make an auditing firm according to the phases of the audit as filed NIA's . For the development of research to primary sources of information was used as the survey staff of the company, personal sources and various bibliographies for information relevant to the project. With the results of the research note that the company has administration shortcomings in its administration because, it has no policy manual for inventory management. Further notes that if the company has an adequate accounting system, this results in that if you are applying IAS 2 Inventories allowing excellent control out entry and exit of goods, storage conditions and physical space is violated for proper treatment. By the results of its evaluation of the company, it was established that the risk of overall control is reliable, it was a 21,47%; Audit also a risk of 37%, are considered optimal, but should be strengthened to keep inventory accurate and reliable. In analyzing the procedures was learned that the inventory exists in the hold is good rotation causing a positive factor for the economy of the company holding the goods for two months